Address to the Heads of Government Conference, March 11, 1994 - St. Vincent and the Grenadines. Prime Minister ([s.n.] [S.l.], 1994)
Examines issues such as the effects of NAFTA on the Caribbean; tourism; the banana industry in the OECS; and the effect of the redirection of the flow of traditional donors.